Late-Type Recurrence at the Port Site of Unexpected Gallbladder Carcinoma After a Laparoscopic Cholecystectomy : Report of a Case - Nakagawa, Satoru; Tada, Tetsuya; Furukawa, Hiroshi; Abe, Masaki; Hatakeyama, Katsuyoshi (Surgery today (Tokyo, Japan), 2000)
A 73-year-old woman had a laparoscopic cholecystectomy for unexpected gallbladder cancer and 9 days later underwent both a liver bed resection and lymph node dissection. Four years later, she underwent a further resection of a port site recurrence of gallbladder cancer and no other site of recurrence was observed. The seeding of cancer cells during the removal of the resected gallbladder might have caused this tumor. This case may show that the port site recurrence did not necessarily indicate an incurable stage of the disease. In addition, an excision of the recurrent tumor also appeared to eliminate the disease in the patient.